1995
DOI: 10.1103/physrevlett.74.4376
|View full text |Cite
|
Sign up to set email alerts
|

CPTTests in the Neutral Kaon System

Abstract: Fermilab experiment E773 has measured the phases 4+ = 43. 53'~0 . 97' and 400 -4+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 6 publications
1
70
0
Order By: Relevance
“…For example, the E773 data were collected over several months [3]. Effects of the Earth's motion on the meson velocities and orientations must therefore be considered.…”
Section: (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the E773 data were collected over several months [3]. Effects of the Earth's motion on the meson velocities and orientations must therefore be considered.…”
Section: (1)mentioning
confidence: 99%
“…Among the various tests of CPT [2], the sharpest published bounds are obtained with the neutralkaon system. As an example, the CPT figure of merit r K ϵ jm K 2 m K j͞m K has recently been constrained to r K , 1.3 3 10 218 at the 90% confidence level by the experiment E773 at Fermilab [3,4].In neutral-meson interferometry, bounds on CPT violation are extracted using a phenomenological description of the meson time evolution. Denote by P 0 any of the possible neutral mesons…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that the theory maintains many of the other usual properties of the standard model besides Lorentz and CPT symmetry, such as electroweak breaking, energy-momentum conservation, the spin-statistics connection, microcausality, and observer Lorentz covariance. In addition to the atomic experiments described here, the standard-model extension has been used to analyze Lorentz and CPT tests with neutral mesons [27,28], photon experiments [5,25,29], and baryogenesis [30].…”
Section: Standard-model Extensionmentioning
confidence: 99%
“…Given the small value of (1 − |η 00 /η +− |), the value of φ 00 − φ +− provides a measure of CP T violation in K 0 L → 2π decay. Results from CERN [1] and Fermilab [2] indicate no CP T -violating effect.…”
mentioning
confidence: 99%